The returning butterflies: Social entrepreneurs and sustainability in ecotourism - Christine Revsbech Jensen; Luise Li Langergaard (Forskning og Forandring, 2020)
This article is based on a field study of adventure ecotourism in Nepal, and aims to explore how social entrepreneurs operationalize and practice sustainable development in this field. The qualitative data material was analyzed from a critical hermeneutical approach. The article reviews views of currently discussed, multi-dimensional sustainability models representing the idea that sustainability can be developed with an eye to the dynamics between society, the environment, and economy. These dimensions of sustainability were brought into the analysis of the case organization, offering empirical practice perspectives on: the articulation of fundamental values put into action; efforts towards ecology; and the involvement of the local community. All of these have an emphasis on education as a tool for change. Based on examples and critical insight into current sustainability models, the article concludes: that it is of central importance to the case study organization to find a balance between the dimensions; that they are interconnected; and that one aspect of this implies viewing economy as a means rather than an end in itself.